A buffer‐aware fleet‐based cooperative H.264/SVC streaming over vehicular networks. (18th June 2013) - Lee, C‐H.; Huang, C‐M.; Yang, C‐C.; Tsai, W‐P.
SUMMARY Because of of the characteristics of high mobility, time varying and dynamic topology, how to provide multimedia streaming service for connected vehicles becomes one emerging and popular technical research. The motivation of this paper is to utilize cooperation among neighboring vehicles for video streaming's quality improvement over vehicular networks. In the proposed cooperative streaming scenario, a connected vehicle requests a video stream from the Internet by using its 3G/3.5G interface, which may not have enough bandwidth to receive good quality of video. Thus, the vehicle is suggested to ask neighboring members belonging to the same fleet to download the requested video data by using their 3G/3.5G interfaces. Then, neighboring members should forward video data to the requested vehicle by using another wireless technique, for example, dedicated short range communication (DSRC). Regarding the differentiation between the two access networks, that is, 3G/3.5G network and DSRC network, a buffer‐aware scheduling mechanism based on layered streaming is designed in this paper to adapt to the networking situation of the vehicular networks. Two selection algorithms are proposed to select neighboring vehicles from the fleet. According to our simulation results, the 3G/3.5G‐based selection algorithm is suitable to improve video quality for vehicles at low speeds. On the other hand, the DSRC‐based selection algorithm can get better performance when vehicles move at high speeds or too many data are transmitted among vehicles.Copyright © 2013 John Wiley & Sons, Ltd.